ChemInform Abstract: The Phosphorus‐Claisen Condensation. Issue 23 (16th May 2013) - Gavara, Laurent; Gelat, Fabien; Montchamp, Jean‐Luc
Abstract The title reaction between different phosphorus‐stabilized carbanions and a phosphorus electrophile offers a convenient synthesis of 1, 1‐bisphosphorus compounds.